2014
DOI: 10.1111/1467-8489.12092
|View full text |Cite
|
Sign up to set email alerts
|

Convenience yield and the theory of storage: applying an option-based approach

Abstract: We propose that an options-based approach is a superior alternative to the traditional cost-of-carry method to model both the behaviour of convenience yields and the commodity price responses to changes in inventory levels. This approach is shown to be more robust and avoids the simplifying assumptions embedded in cost-of-carry valuation which fully accounts for the non-negativity constraint on inventory. Unlike the cost-of-carry approach, the options-based approach does not treat the convenience yield as an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The respective regressions follow the work done by Kucher and Kurov (2014), Omura and West (2015) and Fattouh (2009) and are represented as:…”
Section: Appendix D Methodology and Empirical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The respective regressions follow the work done by Kucher and Kurov (2014), Omura and West (2015) and Fattouh (2009) and are represented as:…”
Section: Appendix D Methodology and Empirical Resultsmentioning
confidence: 99%
“…A number of studies have shown that a optionsbased approach to storage valuation models is superior to traditional methods that rely on simple calculations or estimates of the cost of carry, basis and convenience yield (Omura and West 2015). It is important to note that these studies focus exclusively on calendar-spread options, which are positions established by selling a call (i.e., the right to buy in the future) on a specific volume of an asset, at a given price, and buying a call on the same amount further in the future, at the same price.…”
Section: The Relationship Between Market Structure and Inventoriesmentioning
confidence: 99%
“…More recent studies focused on the effects of private versus public stocks on food price volatility (Chavas and Li 2017), on the responses of commodity price to changes in stock levels (Omura and West 2014), and on the transmission and volatility of commodity prices (Bakucs et al 2012;Hassouneh et al 2017). None of these directly estimated the crowding out of private stocks by public stocks.…”
Section: Previous Studiesmentioning
confidence: 99%
“…As stabilisation fell out of favour, attention turned to the use of futures markets for producer hedging (Gruen ; Goss ; Bond et al . ; Fraser ; Simmons and Rambaldi ) and to the use of private storage to manage uncertainty (Omura and West ).…”
Section: Price Uncertainty and Price Stabilisationmentioning
confidence: 99%